2004
DOI: 10.1007/s00442-004-1676-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of tree biomass and wood litter to disturbance in a Central Amazon forest

Abstract: We developed an individual-based stochasticempirical model to simulate the carbon dynamics of live and dead trees in a Central Amazon forest near Manaus, Brazil. The model is based on analyses of extensive field studies carried out on permanent forest inventory plots, and syntheses of published studies. New analyses included: (1) growth suppression of small trees, (2) maximum size (trunk base diameter) for 220 tree species, (3) the relationship between growth rate and wood density, and (4) the growth response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
129
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 64 publications
5
129
1
2
Order By: Relevance
“…Episodic disturbance events with return frequencies greater than ∼30 y are not well represented in the existing Amazon network where plots were monitored for 4.0-21.7 y (mean of 10.9 y) up to the early 2000s (5). A plot-based study in the Central Amazon, for example, found that the largest gap occurring on 56 separate census intervals varying from 1 to 5 y on 21 single hectare permanent plots included only one eight-tree blowdown cluster, and only seven events exceeding six trees per cluster (24,25). Thus, a plot-based mortality rate estimate for the Central Amazon of 1.02% stems·y −1 (24) was entirely missing the mortality contribution of events exceeding eight trees per cluster.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Episodic disturbance events with return frequencies greater than ∼30 y are not well represented in the existing Amazon network where plots were monitored for 4.0-21.7 y (mean of 10.9 y) up to the early 2000s (5). A plot-based study in the Central Amazon, for example, found that the largest gap occurring on 56 separate census intervals varying from 1 to 5 y on 21 single hectare permanent plots included only one eight-tree blowdown cluster, and only seven events exceeding six trees per cluster (24,25). Thus, a plot-based mortality rate estimate for the Central Amazon of 1.02% stems·y −1 (24) was entirely missing the mortality contribution of events exceeding eight trees per cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Episodic disturbances create patches with a large amount of coarse woody debris (CWD), and the time required for the decomposer community to consume this CWD and release CO 2 is much faster in Amazon forests than biomass recovery following disturbance (24). Thus, recent tree fall gaps in the early stages of succession will act as large carbon sources, followed by decades of slow carbon accumulation as trees fill the gap and species community composition changes over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detectable highmortality areas ranged from 5-10 fallen trees (Text S2) occupying single pixels, to blowdown patches of ∼30 ha in size. The disturbance produced by the squall line across the Manaus region encompassed 2668 ha causing estimated mortality of 0.32 ± 0.05 (SD) million trees, equivalent to a total biomass loss of 85 ± 25 (SD) Gg C which will be respired to the atmosphere over an ∼18 year period [Chambers et al, 2004]. The MC model predicted a mortality of 0.5 ± 0.056 million trees, equivalent to a total biomass loss of 128 ± 14 Gg C (using Figure S5).…”
Section: Resultsmentioning
confidence: 99%